Analysis of Factors Causing Traffic Accidents on Sultan Agung Street, Bekasi - Andri Irfan Rifai; Eka Satria Aulia (NAROTAMA UNIVERSITY, Indonesia, 2019)
Sultan Agung Street is the main road in Bekasi City which has a length of 5.5 km. On the Sultan Agung Street, there are many settlements and public facilities. However, this condition was not matched by adequate road infrastructure and public transportation facilities and infrastructure. This causes an increase in the volume of traffic and potential for accidents on Sultan Agung street. The purpose of this study was to determine the dominant causal factors of accidents and to determine efforts to prevent accidents on Jalan Raya Sultan Agung with the Upper Control Limit (BKA) and Upper Control Limit (UCL) methods. Based on the analysis of Sultan Agung Bekasi Street included in the category of accident-prone roads because there are two road segments having AEK values ​​exceeding the BKA and UCL values. The coordinate point of the location with the highest AEK value is the third segment with an AEK value of 195 where the BKA value is 122,894 and the UCL value is 119,333. The most common type of accident is a Front-Rear hit by 37.5% of the total number of accidents. Time of accidents most often occurs at night with a percentage of 56% of the number of accidents.